2019
DOI: 10.1108/bfj-01-2019-0033
|View full text |Cite
|
Sign up to set email alerts
|

Consumer insight on a snack machine producing healthy and customized foods at point of consumption

Abstract: Purpose The purpose of this paper is to investigate a healthy snacking and on-the-go eating concept, “Healthy Snack Machine” (HSM) that produces freshly made food and enables customization of the product at site of purchase and consumption. Design/methodology/approach The study applied qualitative and quantitative consumer research methods and used iterative co-creation approach, meaning that the HSM concept was developed by consumer input during different phases. Specifically, the research included three qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 18 publications
0
15
0
2
Order By: Relevance
“…The availability of nutritional information has usually been mentioned by consumers as an important factor affecting their purchasing decision [ 7 , 26 , 27 ]. Still, previous studies found out that there is a big number of users who do not follow the nutritional information at all [ 7 , 28 ], and hunger and convenience drive the purchases made at vending machines [ 29 , 30 ]. In addition to nutritional information, allergens and information of the origin of the ingredients were previously reported to be valuable for the consumers [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The availability of nutritional information has usually been mentioned by consumers as an important factor affecting their purchasing decision [ 7 , 26 , 27 ]. Still, previous studies found out that there is a big number of users who do not follow the nutritional information at all [ 7 , 28 ], and hunger and convenience drive the purchases made at vending machines [ 29 , 30 ]. In addition to nutritional information, allergens and information of the origin of the ingredients were previously reported to be valuable for the consumers [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies indicate strong consumer interest in healthier snacking [ 4 , 5 ], which, thus, provides an opportunity to develop new solutions to increase healthier food choices in the snacking category [ 6 ]. In our previous work, we investigated a healthy snacking and on-the-go eating concept, “Healthy Snack Machine” (HSM), that produces freshly made food and enables customization of the product at the site of purchase and consumption [ 7 ]. By using qualitative and quantitative research methods with an iterative consumer co-creation approach, we were able to show that consumers were attracted by a new snacking concept that would help them to consume healthier food and enable customization of the product.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations